2014
DOI: 10.1002/jssc.201400590
|View full text |Cite
|
Sign up to set email alerts
|

Assessing stability-indicating methods for coelution by two-dimensional liquid chromatography with mass spectrometric detection

Abstract: Chromatographic analysis of trace organic impurities/degradants coeluting in the midst of active pharmaceutical ingredient can be challenging given similarities in their structures and differences in their relative levels/intensities. Conventional detection techniques such as diode array detection and mass spectrometry are often inadequate to detect/identify these residual coeluting impurities and could result in a false negative. Application of two-dimensional chromatography to address/evaluate coelution in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…As reported by Stoll and co-workers, sLC × LC is generally applied to the determination of peak purity during method validation as an effective alternative to UV–vis, diode-array, or MS detection. As an example of this application, Venkatramani et al . demonstrated the ability of sLC × LC to resolve structurally similar impurities that eluted in proximity to the main component, with coeluting impurities resolved and detected at levels <0.05% in the presence of the main component.…”
Section: Applicability Of 2d-lcmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported by Stoll and co-workers, sLC × LC is generally applied to the determination of peak purity during method validation as an effective alternative to UV–vis, diode-array, or MS detection. As an example of this application, Venkatramani et al . demonstrated the ability of sLC × LC to resolve structurally similar impurities that eluted in proximity to the main component, with coeluting impurities resolved and detected at levels <0.05% in the presence of the main component.…”
Section: Applicability Of 2d-lcmentioning
confidence: 99%
“…As reported by Stoll and co-workers, 30 sLC × LC is generally applied to the determination of peak purity during method validation as an effective alternative to UV−vis, diode-array, or MS detection. As an example of this application, Venkatramani et al 42 demonstrated the ability of sLC × LC to resolve structurally similar impurities that eluted in proximity to the main component, with coeluting impurities resolved and detected at levels <0.05% in the presence of the main component. Similarly, Shackman et al 43 highlighted the suitability of the sLC × LC for the determination of peak purity of a pharmaceutical formulation containing multiple active components that possessed diverse physicochemical properties.…”
Section: ■ Possibilities In High-throughput and High-resolution Lc Se...mentioning
confidence: 99%
“…2DLC plays an increasingly important role in both proteome research and complex biological samples separation due to its high selectivity, peak capacity, and resolving power. However, the current 2DLC systems have some drawbacks, for example, not only they need two orthogonal columns, multiple sets of pumps, and multiple switching valves, but also the incompatibility of solvents may cause band dispersion or broadening .…”
Section: Introductionmentioning
confidence: 99%
“…Venkatramani et al used a similar "pseudocomprehensive" strategy for the impurity analysis of pharmaceutical components. 13 Demonstration of a multiple heart-cutting 2D-LC system with UV, MS, and CAD detection was made very recently by Zhang et al 14 An extensive setup consisting of six valves for modulation, peak parking, and trapping provided the framework for pharmaceutical impurity analysis. The work was mainly done in a qualitative fashion, and with the exception of sensitivity assessment, no quantitative or repeatability data were provided.…”
mentioning
confidence: 99%
“…As a bridge between comprehensive and heart-cutting modes, selective comprehensive 2D-LC has been introduced by the Stoll group. The benefit of selective comprehensive 2D-LC is that a more detailed view of certain areas in the 1 D chromatogram is obtained, e.g., for peak purity analysis or determination of overlapping components. Venkatramani et al used a similar “pseudocomprehensive” strategy for the impurity analysis of pharmaceutical components . Demonstration of a multiple heart-cutting 2D-LC system with UV, MS, and CAD detection was made very recently by Zhang et al An extensive setup consisting of six valves for modulation, peak parking, and trapping provided the framework for pharmaceutical impurity analysis.…”
mentioning
confidence: 99%